Intermittent theta burst stimulation of the right dorsolateral prefrontal cortex accelerates visuomotor adaptation with delayed feedback. (August 2020) - Song, Yanlong; Adams, Sarah; Legon, Wynn
Abstract: Implicit adaptation to visual rotations during fast reaching is a well-recognized function of the cerebellum. However, there is still no well-established understanding of the neural underpinnings that support explicit processes during visuomotor adaptation. We tested the causative involvement of dorsolateral prefrontal cortex (DLPFC) in an adaptive reaching task by employing excitatory intermittent theta burst stimulation (iTBS) to left or right DLPFC during learning to adapt to a sudden large visual rotation with delayed terminal feedback. Spontaneous resting-state electroencephalography (EEG) signals were recorded before and immediately after the administration of iTBS. iTBS to right DLPFC, compared to left DLPFC or control, induced faster adaptation to the rotation and had a greater adjustment of aiming directions in early adaptation trials. Moreover, resting-state functional connectivity of EEG of the frontal cortex after iTBS predicted subsequent adaptation rate. These results suggest a critical role of right DLPFC in supporting explicit learning in the adaptive reaching task.